Mechanical valve replacement for patients with rheumatic heart disease: the reality of INR control in Africa and beyond - Zilla, Peter; Human, Paul; Pennel, Tim (Frontiers in Cardiovascular Medicine, 2024)
The majority of patients requiring heart valve replacement in low-to middle-income countries (LMICs) need it for Rheumatic Heart Disease (RHD). While the young age of these patients largely prescribes mechanical prostheses, reliable anticoagulation is often unattainable under the prevailing socioeconomic circumstances.Clotted valves presenting for emergency surgery as a consequence of poor adherence to anticoagulation-control are frequent. The operative mortality of reoperations for thrombosed mechanical valves is several times higher than that of tissue valves and long-term results are also disappointing.Under-anticoagulation prevails in these regions and has clearly been linked to poor International Normalised Ratio (INR) monitoring. In industrialised countries, safe anticoagulation is defined as >60-70% of time in therapeutic range (TTR). In LMICs the TTR has been found to be in the twenties to forties.We analysed > 20,000 INR tests in 552 consecutive patients receiving a mechanical valve for RHD. Only 27% of tests were in the therapeutic range with the vast majority (61%) being sub-therapeutic. Interestingly, the post-operative frequency of INR tests of one every 3-4 weeks in year 1 had dropped to less than 1 per year by year 7.LMICs need to use clinical judgement and assess the probability of insufficient INR monitoring prior to uncritically applying Western guidelines predominantly based on chronological age. Identification of high-risk subgroups regarding defaulting anticoagulation control should take the adherence-history of the >50% patients with RHD into account who were in chronic atrial fibrillation prior to surgery as well as geographic and socioeconomic circumstances.